2010
DOI: 10.1088/0957-4484/21/28/285105
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific cellular uptake of surface-functionalized quantum dots

Abstract: We report a systematic empirical study of nanoparticle internalization into cells via non-specific pathways. The nanoparticles were comprised of commercial quantum dots (QDs) that were highly visible under a fluorescence confocal microscope. Surface-modified QDs with basic biologically significant moieties, e.g. carboxyl, amino, and streptavidin, were used, in combination with surface derivatization with polyethylene glycol (PEG) for a range of immortalized cell lines. Internalization rates were derived from i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
116
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(126 citation statements)
references
References 42 publications
10
116
0
Order By: Relevance
“…The observed variations in timing of uptake between the cell lines (Figure 2A and B) may also be influenced by cell-related specificity of internalization mechanisms for quantum dots. It should be noted that phases 1 and 2 of quantum dot distribution in the cells were found earlier in the studies reported by Hoshino et al, 16 Clift et al, 20 and Jiang et al, 19 Kelf et al, 14 Williams et al, 15 and Corsi et al, 17 which showed formation of vesicular structures spread in the cytoplasm corresponding to phase 2. Phase 3, ie, localization of vesicular structures in the perinuclear region, was described by Zhang et al 22 and Xiao et al, 23 and reviewed by Parak et al 33 Phase 4 resembles the data on formation of multivesicular body-like structures and their redistribution in cytoplasm presented by Yuan et al 18 and Jiang et al 19 However, there has been no presentation of an overall picture illustrating the time-dependent nature of natural uptake and distribution of nontargeted negatively charged quantum dots in living cells.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The observed variations in timing of uptake between the cell lines (Figure 2A and B) may also be influenced by cell-related specificity of internalization mechanisms for quantum dots. It should be noted that phases 1 and 2 of quantum dot distribution in the cells were found earlier in the studies reported by Hoshino et al, 16 Clift et al, 20 and Jiang et al, 19 Kelf et al, 14 Williams et al, 15 and Corsi et al, 17 which showed formation of vesicular structures spread in the cytoplasm corresponding to phase 2. Phase 3, ie, localization of vesicular structures in the perinuclear region, was described by Zhang et al 22 and Xiao et al, 23 and reviewed by Parak et al 33 Phase 4 resembles the data on formation of multivesicular body-like structures and their redistribution in cytoplasm presented by Yuan et al 18 and Jiang et al 19 However, there has been no presentation of an overall picture illustrating the time-dependent nature of natural uptake and distribution of nontargeted negatively charged quantum dots in living cells.…”
Section: Discussionsupporting
confidence: 57%
“…Internalization of quantum dots can occur via several possible primary steps, ie, adsorption of proteins from the culture medium onto the surface of the quantum dots, followed by their internalization via receptor-mediated pathways 14 or nonspecific binding and clustering of the nanoparticles near cationic sites on the plasma membrane, triggering receptors and inducing subsequent endocytosis 12 ( Figure 7). The uptake process begins with adherence of quantum dots to cell surface receptors present in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active transport systems play a key role in the intracellular transport of macromolecules and NP. Extensive studies have shown that NP internalization mainly occurs via endocytotic pathways and depends on NP properties (e.g., size, charge, functionalization) as well as on the cellular origin and physiology (Kelf et al 2010;Pi et al 2010;Tan et al 2010). Some authors report presence of transtrophoblastic channels which are thought to be membrane-lined tubular systems that originate from membrane invaginations of the basal syncytiotrophoblastic surface and cross the cell towards its apical surface (Kertschanska et al 1997;Benirschke and Kaufman 2000).…”
Section: The Structure and Function Of The Placental Barriermentioning
confidence: 99%
“…However, very little scrutiny has been directed at pure PEG in this regard, pre-sumably because of the assumed lack of interaction implicit in improved 'stealth'. Questions nonetheless persist about the uptake of nanoparticles with a pure-PEG corona [47,48].…”
Section: Introductionmentioning
confidence: 99%